Male Seminal Relaxin Contributes to Induction of the Post-mating Cytokine Response in the Female Mouse Uterus - Glynn, Danielle J.; Heng, Kee; Russell, Darryl L.; Sharkey, David J.; Robertson, Sarah A.; Anand-Ivell, Ravinder; Ivell, Richard (Frontiers in Physiology, 2017)
The hormone relaxin is important in female reproduction for embryo implantation, cardiovascular function, and during labor and lactation. Relaxin is also synthesized in males by organs of the male tract. We hypothesized that relaxin might be one component of seminal plasma responsible for eliciting the female cytokine response induced in the uterus at mating. When recombinant relaxin was injected into the uterus of wild-type (Rln+/+) mice at estrus, it evoked the production of Cxcl1 mRNA and its secreted protein product CXCL1 in 4 of 8 animals. Mating experiments were then conducted using mice with a null mutation in the relaxin gene (Rln-/- mice). qRT-PCR analysis of mRNA expression in wild-type females showed diminished uterine expression of several cytokine and chemokine genes in the absence of male relaxin. Similar differences were also noted comparing Rln -/- and Rln+/+ females mated to wild-type males. Quantification of uterine luminal fluid cytokine content confirmed that male relaxin provokes the production of CXCL10 and CSF3 in Rln+/+ females. Differences were also seen comparing Rln-/- and Rln+/+ females mated with Rln-/- males for CXCL1, CSF3 and CCL5, implying that endogenous relaxin in females might prime the uterus to respond appropriately to seminal fluid at coitus. Finally, pan-leukocyte CD45 mRNA was increased in wild-type matings compared to other combinations, implying that male and female relaxin may trigger leukocyte expansion in the uterus. We conclude that male and/or female relaxin may be important in activating the uterine cytokine/chemokine network required to initiate maternal immune adaptation to pregnancy.